Socio-demographic and antenatal care-related factors associated with early post-partum family planning use in Ethiopia: evidence from Ethiopian Demographic and Health Survey 2016 data - Melaku Hunie Asratie; Getayeneh Antehunegn Tesema; Dagmawi Chilot; Dagmawi Chilot; Fantu Mamo Aragaw; Mehari Woldemariam Merid; Daniel Gashaneh Belay; Daniel Gashaneh Belay (Frontiers Media S.A., 2023)
IntroductionInitiation of family planning in the early post-partum period is a strategic move to reduce maternal, neonatal, and child mortality due to the negative consequences of short interbirth interval and the complications of unintended pregnancy. Antenatal care (ANC) is the noteworthy predictor of scaling up early initiation of post-partum family planning (PPFP) and preventing unintended pregnancy before menses resume. Despite the great role of ANC, information is scant about the effect of content, timing, and the number of ANC visits on the early initiation of PPFP in Ethiopia.ObjectiveThis study aimed to assess the association of ANC services with the early initiation of PPFP in Ethiopia.MethodsThe study was based on Ethiopian Demographic and Health Survey 2016 data, which was a cross-sectional survey from 18 January 2016 to 27 June 2016. A total weighted sample size of 2,920 post-partum women was included. A multilevel logistic regression model was used because of the hierarchical data, and variables with a p-value of ≤0.2 in the bivariable multilevel analysis were taken to multivariable multilevel analysis. An adjusted odds ratio with a 95% confidence interval (CI) was used to declare both the direction and strength of the association, and variables with a p-value of <0.05 were considered as statistically significant for the outcome variable.ResultsThe early initiation of PPFP was 20.4%. Women with at least four ANC visits [adjusted odds ratio (AOR) = 1.31; CI 1.12-2.32], women who started ANC within the first trimester (AOR = 1.25; CI 1.10-2.23), complete routine ANC (AOR = 1.11; CI 1.01-2.03), post-natal care (AOR = 1.45; CI 1.19-1.87), resumption of menses (AOR = 1.67; CI 1.18-1.93), urban residency (AOR = 2.14; CI 1.18-2.51), and high community women's education (AOR = 1.71; CI 1.51-2.11) were variables significantly associated with the early initiation of PPFP.ConclusionThe early initiation of PPFP in Ethiopia was very low. Attention needs to be given to the quality of ANC, post-natal care, resumption of menses, residency, and community-level education of women to increase the prevalence of the early initiation of PPFP in Ethiopia. Therefore, the government should design a program targeting the quality of ANC in rural communities, considering women without menses and scaling up the education of women at the community level to the culture of the early initiation of PPFP in order to achieve reduced maternal, neonatal, and child mortality.